(untitled) (Eurasian Scientific Herald, 2023)
Based on the analysis of recent literature data, the authors note that urgent complications in volvulus of the sigmoid colon, Payr’s disease, cicatricial adhesive disease, diverticular disease of the left half of the colon remain extremely relevant, due to the high incidence of postoperative complications and mortality during the formation of primary anastomoses, which due to the lack of optimal treatment and diagnostic algorithms and omissions in surgical tactics, as well as long-term disability in colostomy patients. Summing up, the authors note that one of the main ways to prevent suture failure of interintestinal anastomoses is the choice of the optimal method of anastomosis formation, as well as the development of a primary delayed "U-shaped" end-to-side colonic anastomosis, which allows to reduce the time and improve the results of recovery operations.